SUKUK MUDHÂRABAH - Muhammad Fadlilah Fauzulhaq (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This can be beneficial for both parties. Surplus spending unit parties (shâhib al-mâl) can include their funds to deficit spending units (emiten/mudhârib). It manages the funds in the business sectors that are allowed by the sharia with Mudaraba contract and/or contract in accordance with the times.